International good practice in information literacy education - Lyn Robinson; David Bawden (Knjižnica)
Purpose: A report is given on a survey of international good practices in information literacy education, the first stage of an Erasmus+ project, Information Literacy Online (ILO), which is creating a multi-lingual and multi-cultural MOOC for information literacy instruction. Methodology/approach: The survey was based on a selective identification and analysis of published literature and Internet sources, qualified by expert opinion. Results: The results are summarised in five sections: definitions, models, content, and contexts for information literacy; frameworks and methods for teaching and learning of information literacy; information literacy learning materials; multicultural and multilingual aspects of information literacy education; use of MOOCs for information literacy education. Research limitations: The review is selective rather than comprehensive, and focuses on those issues of most significance for the development of the ILO MOOC. Originality/practical implications: Although the findings are directed to support the development of the ILO MOOC, it is hoped that they may be of more general interest to those involved in information literacy instruction.